2012
DOI: 10.1253/circj.cj-12-0463
|View full text |Cite
|
Sign up to set email alerts
|

Beam-Hardening Correction for Virtual Monochromatic Imaging of Myocardial Perfusion via Fast-Switching Dual-kVp 64-Slice Computed Tomography

Abstract: here has been a growing interest in using computed tomography (CT) for combined assessment of myocardial perfusion and morphology of the coronary artery. 1 First-pass coronary artery imaging using CT has the potential to assess the physiologic relevance of a coronary artery lesion. 2, 3 In conventional single-kVp CT images, however, a considerable decrease in the myocardial CT value is often seen at the posterobasal wall, mimicking perfusion defects, and such decreases have been attributed to beam-hardening (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…On the contrary, fast kVp‐switching spectral CT enables near‐simultaneous acquisition of high and low energy datasets allowing the implementation of projection‐based material decomposition algorithms. These algorithms have been shown to greatly reduce BH artifacts and allow for better image quality compared to DSCT scanning . To our knowledge, this is the first study employed to assess iodine concentration accuracy using a modern fast kVp‐switching dual energy CT scanner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, fast kVp‐switching spectral CT enables near‐simultaneous acquisition of high and low energy datasets allowing the implementation of projection‐based material decomposition algorithms. These algorithms have been shown to greatly reduce BH artifacts and allow for better image quality compared to DSCT scanning . To our knowledge, this is the first study employed to assess iodine concentration accuracy using a modern fast kVp‐switching dual energy CT scanner.…”
Section: Discussionmentioning
confidence: 99%
“…These algorithms have been shown to greatly reduce BH artifacts and allow for better image quality compared to DSCT scanning. 5,6,9 To our knowledge, this is the first study employed to assess iodine concentration accuracy using a modern fast kVp-switching dual energy CT scanner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With stress myocardial perfusion CT, beam-hardening arising from high-density iodinated contrast hampers accurate assessment of myocardial perfusion. Studies using ex vivo hearts and phantom models demonstrated improved detection of myocardial perfusion defects by reduction of beam-hardening artifacts mimicking perfusion deficits using fast-switching kVp DECT technology (37,38). A clinical study by So et al showed rapid kV-switching projection-based DECT to improve ischemia detection by elimination of beam-hardening artifacts (4).…”
Section: Minimizing Image Artifacts Using Dual-energy Ctmentioning
confidence: 99%
“…Recent study shows that image-based beam-hardening correction algorithm is feasible for the correction of beam-hardening artifacts that mimic perfusion defects. The beam-hardening correction used in the study was an image-based correction algorithm that enables individual estimation of the beam hardening from high-enhancing material and water-enhancing material for accurate calculation of the amount of beam hardening and to reconstruct a corrected image [ 74 , 75 ]. The study also demonstrates that virtual monochromatic images generated using fast-switching dual-kVp technology are feasible for the correction of beam-hardening artifacts in myocardial CT imaging [ 71 ].…”
Section: Limitations and Prospect Of Ct Perfusionmentioning
confidence: 99%